A Note on Leigh Hunt, Nicholas Carrington, and The Liberal - Roe, Nicholas (Romanticism and Victorianism on the Net, 2011)
Plymouth poet Nicholas Carrington's poem of bon voyage for Leigh Hunt, 'To a Friend, On His Approaching Voyage to Pisa' (1822), marks the beginning of Hunt's journey to join Lord Byron and P. B. Shelley in publishing  the Liberal  magazine. The poem offers a sidelight on some iconic events of Anglo-Italian Romanticism, and suggest that Carrington's other works deserve more attention than they have so far received.